IMPLEMENTATION OF BIM (BUILDING INFORMATION MODELING) ON CALCULATION OF QUANTITY TAKE OFF HEAP IN PASURUAN-PROBOLINGGO TOLL ROAD SECTION 4 PROJECT - Fajar Sodiq Febriansyah (Universitas Muhammadiyah Surabaya, 2021)
The progress of construction industry in Indonesia has experienced very rapid development in the infrastructure sector, as proven by the many infrastructure developments in recent years. Quantity take-off is one of the contractor's efforts by calculating volume which will later be used as material for preparing bill of quantity in tenders and later also used as material for procurement. This is because contractors who can accurately carry out quantity take-offs will get several benefits, such as efficiency of incoming materials because they are in accordance with actual conditions. Autodesk civil 3D is a tool or application based on Building Information Modeling (BIM) which is capable to do quantity take-off. In this study, it will be discussed how the advantages and disadvantages of auto-desk civil 3D in carrying out quantity take-off on the volume of the stockpile compared to the method that has been used so far, namely calculating the volume using images from Autocad and with the assistance of Microsoft excel. The results of calculations using BIM in this study showed an increase in volume by 0.027%, a decrease in time by 80%, and an increase in costs by 37% when compared to conventional calculations. Keywords : BIM, Quantity Take-off, Autodesk Civil 3D